Photoluminescence identification of surface contaminants on zinc oxide from their phase transitions. Issue 6 (3rd July 2018) - Cui, M.; Jin, H.; Xi, L.; Wang, Y.; Townsend, P. D.
Abstract: The spectra of photoluminescence (PL) from a zinc oxide (ZnO) crystal included an unusual feature of an ultraviolet (UV) emission at a higher energy than the ZnO interband transitions. The energy of this UV emission varied with temperature and included two discontinuous energy steps in the temperature range from 78 to 700 K. The temperature values of the steps match phase transition temperatures of ethanol. Ethanol was used during sample cleaning and can be trapped in the form of nanoparticles inclusions. Both the intrinsic and defect site, PL signals have different temperature dependencies from those of bulk crystals, as seen during radioluminescence. The origins of the changes are discussed.